2020
DOI: 10.3390/ani10071236
|View full text |Cite
|
Sign up to set email alerts
|

Review of Livestock Welfare Indicators Relevant for the Australian Live Export Industry

Abstract: Animal welfare is an important issue for the live export industry (LEI), in terms of economic returns, community attitudes and international socio-political relations. Mortality has traditionally been the main welfare measure recorded within the LEI; however, high mortality incidents are usually acted upon after adverse events occur, reducing the scope for proactive welfare enhancement. We reviewed 71 potential animal welfare measures, identifying those measures that would be appropriate for use throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 93 publications
0
7
0
2
Order By: Relevance
“…However, the attitudes toward animal welfare and the perceptions towards its assessment within the industry have not been investigated. Frameworks for animal welfare assessment on Australian farms [17] and in export supply chains [18] are under development and, once adopted, should bring more understanding about the affective state of animals in production systems, and potentially alter public perception. To the authors knowledge, despite the public concern, there is little transparency about the daily routine care of animals on board livestock vessels.…”
Section: Introductionmentioning
confidence: 99%
“…However, the attitudes toward animal welfare and the perceptions towards its assessment within the industry have not been investigated. Frameworks for animal welfare assessment on Australian farms [17] and in export supply chains [18] are under development and, once adopted, should bring more understanding about the affective state of animals in production systems, and potentially alter public perception. To the authors knowledge, despite the public concern, there is little transparency about the daily routine care of animals on board livestock vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Similar incidents have continued to recur and investigations reveal failures of monitoring and enforcement of ESCAS in destination countries, in both approved and nonapproved facilities, most often revealed by the efforts of the various welfare agencies (38). The ongoing concerns have also led to a recent research review of 71 potential animal welfare indicators, categorized as animal, environmental and resourcebased measures that would be appropriate for use throughout the LEI for feeder and slaughter livestock species in the 3 LEI sectors: (1) Australian facilities; (2) vessel; and (3) destination country facilities (39). The review identified 38 (sector 1), 35 (sector 2), and 26 (sector 3) measures currently being collected plus 20, 25, and 28 measures that are relevant to each LEI sector (sectors 1, 2, 3, respectively), and that could be developed and integrated into a future benchmarking system (39) should the LEI's continue, presumably as a transition industry until importing countries agree that processed meat is a preferred product to live animals.…”
Section: Livestock Transportation Welfarementioning
confidence: 99%
“…To appropriately apply behavioral assessments of welfare, it is important to understand several of the most commonly used concepts of animal welfare. As there are numerous tools to measure welfare [20][21][22][23][24][25][26][27][28][29], there are also numerous constructs of welfare itself [30]. It is possible for the decision of how to define welfare to reflect one's own philosophical view on animal rights and animal sentience, with each concept leading to a different use of behavioral measures.…”
Section: Behavior In Common Concepts Of Animal Welfarementioning
confidence: 99%